Perencanaan Sistem Penerangan Jalan Umum di Kampus UNIDA - Mahdi Syukri; Teuku Multazam; Abdul Malek (Fakultas Teknik, 2021)
Public street lighting must comply with the Indonesian national standard (SNI) regarding specifications for street lighting in urban areas, and general requirements for electrical installations (PUIL) 2011. This aims to provide security, smoothness, and comfort for road users. The main requirement is to meet the lighting standards of this type of lamp. Planning electrical installations for street lamp lighting must have five criteria in order to produce quality and comfort in street lamp lighting, one aspect that is seen is based on lighting. Iskandar Muda University has four main roads that do not yet have street lights. The condition will certainly have a negative impact on universities, students and the surrounding community when carrying out activities. Therefore, it is necessary to analyze the planning of street lighting in the campus environment so as to produce optimal lighting quality. The optimal value is seen based on the suitability of lighting, pole height and the type of lamp to be used against applicable standards. The calculation results show that the use of the optimal number of lamps on roads in the area is 21 units with the type of lamp used is SOX 135 watts. The intensity obtained at that location is 11.5 lux to 14.4 lux.